Loads in furrow opening tools for seeders on no-tillage systems - Mion, Renildo Luiz; Benez, Sérgio Hugo [UNESP] (FapUNIFESP (SciELO), 2008)
The individual evaluation of mechanisms for opening furrows to drop the seeds in a no-tillage seeders cultivation assists the companies in the sizing of opening tools of the ground, that search for minor energy petition and for diminishing the ground area mobilized. Therefore this work had the aim of evaluate the efforts of five different mechanisms of opening of ridge of seeding of direct plantation varyng the vertical load. The experiment was installed in one ground classified as Dystroferric Red Nitosol. The used experimental delineation was of the one randomized blocks in a factorial project 5 × 4, constituted a the following factors: five mechanisms of furrow opening (even disk - DL, corrugated disk - DC, ondulated disk - DO, double disk DD and furrow rod - F) and four vertical loads (750, 1500, 2250 and 3000 N). To measure the forces in the studied treatments a dynamometer with sensitivity in the directions was used horizontal, lateral and vertical direction. The evaluation showed that the interaction between mechanisms of opening of ridge and vertical load was not significant, however the factors were significant when analyzed individually. The connecting rod promoted mobilization of the ground with smaller draft of horizontal effort reaching depths of work. The work showed that the vertical load influenced the depth of work of the mechanisms of ridge opening. The mechanisms of ridge opening of record type need vertical force to penetrate into the ground.
Esforços em ferramentas rompedoras de solo de semeadoras de plantio direto
Keywords: 3-D load; Depth of work; Dynamometer; Mechanism of opening of ridge